“You can know an analysis by the source of its data”. A conceptual and methodological review of databases on armed conflict in Colombia - Espinosa M, Nicolás; Universidad de Antioquia (Editorial Pontificia Universidad Javeriana, 2009)
In Colombia, there are quantitative databases on armed conflict, some of them public and open-access. This paper reviews the main theoretical and methodological traits in some of those databases and their main features when defining and measuring political violence. Based on the results of a research performed in a Colombian region, several methodological issues will be presented in order to process —statistically, spatially and cartographically― the information delivered by those databases. After the exposition, several procedures are described, which allowed to measure differences among databases. Those contents are addressed aiming to show the consequences that using one or another database has in the quantitative analysis of armed conflict, since the results of those analyses will depend on the source used.